2019
DOI: 10.1029/2018gl081339
|View full text |Cite
|
Sign up to set email alerts
|

Natural Analogue Constraints on Europa's Non‐ice Surface Material

Abstract: Non‐icy material on the surface of Jupiter's moon Europa is hypothesized to have originated from its subsurface ocean and thus provide a record of ocean composition and habitability. The nature of this material is debated, but observations suggest that it comprises hydrated sulfate and chloride salts. Analogue spectroscopic studies have previously focused on single‐phase salts under controlled laboratory conditions. We investigated natural salts from perennially cold (<0 °C) hypersaline springs and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…The waters are anoxic upon exiting the diapirs and become rapidly oxidised at the surface 2,42 . The springs that have been previously characterised with regards to their chemistry and mineralogy are Lost Hammer (LH), Gypsum Hill (GH) and Colour Peak (CP) 2,38,42,43 . These studies have indicated that the mineralogy of deposits at these spring sites are predominantly calcite (CaCO 3 ), halite (NaCl), thenardite (Na 2 SO 4 ), mirabilite (Na 2 SO 4 •10H 2 O), gypsum (CaSO 4 •2H 2 O) and elemental sulfur (S°) 38,42,43 , but variations exist between springs as a result of differences in their fluid geochemistry.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The waters are anoxic upon exiting the diapirs and become rapidly oxidised at the surface 2,42 . The springs that have been previously characterised with regards to their chemistry and mineralogy are Lost Hammer (LH), Gypsum Hill (GH) and Colour Peak (CP) 2,38,42,43 . These studies have indicated that the mineralogy of deposits at these spring sites are predominantly calcite (CaCO 3 ), halite (NaCl), thenardite (Na 2 SO 4 ), mirabilite (Na 2 SO 4 •10H 2 O), gypsum (CaSO 4 •2H 2 O) and elemental sulfur (S°) 38,42,43 , but variations exist between springs as a result of differences in their fluid geochemistry.…”
mentioning
confidence: 99%
“…The springs that have been previously characterised with regards to their chemistry and mineralogy are Lost Hammer (LH), Gypsum Hill (GH) and Colour Peak (CP) 2,38,42,43 . These studies have indicated that the mineralogy of deposits at these spring sites are predominantly calcite (CaCO 3 ), halite (NaCl), thenardite (Na 2 SO 4 ), mirabilite (Na 2 SO 4 •10H 2 O), gypsum (CaSO 4 •2H 2 O) and elemental sulfur (S°) 38,42,43 , but variations exist between springs as a result of differences in their fluid geochemistry. For example, LH fluids have higher concentrations of sodium than CP fluids, but lower concentrations of sulfide (0.14 mM) and calcium (24.43 mM) than CP (1.8 mM and 33.23 mM respectively) 43 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In any case, beyond of the very ambitious goals of the hypotheses about the origin of life, herein it is just showed that a potential wide organic chemistry can be produced from very simple carbon sources where the ice-liquid water interfases play an active role. Thus, more comprehensive and systematic synthetic studies are needed, considering other temperature ranges below 0 • C, pressures, doses of radiation, concentrations of reactants and the presence of sulfates (due to the emplacement of endogenic sulfates on Europa's surface, Fox-Powell et al, 2019), that simulate the subsurface water oceans in liquid-solid equilibrium to design the best chromatography tools and finest analytical methods for space exploration with the objective of collecting suitable data about the possible habitability of a particular icy environment. On the other hand, interpolation of the data about the plausible organics found in these icy places together with the statistical studies performed via simulation experiments could help to interpret and understand the planetary conditions under which this plausible organic chemistry has been produced.…”
Section: Potential Organic Chemistry In Icy Ocean Worldsmentioning
confidence: 99%